Faktor-Faktor yang Mempengaruhi Persistensi Laba (Studi Kasus Pada Perusahaan Perbankan dan Jasa Keuangan yang Terdaftar di Bursa Efek Indonesia) - Ahmad Basid Hasibuan; Riana Syintia Rahesti (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2021)
This study aims to examine the factors that influence earnings persistence on banking and financial service companies listed on the Indonesia Stock Exchange (IDX) period 2014-2018. This research uses quantitative methods with purposive sampling. There are 33 sample companies with a total of 165 observations. Data analysis in this study uses the classic assumption test and hypothesis testing using multiple linear regression methods. The results showed that temporary differences had a positive and significant effect on earnings persistence. Permanent differences have a negative and significant effect on earnings persistence. Operating cash flow has a positive and significant effect on earnings persistence. While the independent variable is able to explain the dependent variable 54.7%, while the rest is explained by other variables outside this research variable